1977
DOI: 10.1073/pnas.74.4.1647
|View full text |Cite
|
Sign up to set email alerts
|

The cost of evolution and the imprecision of adaptation.

Abstract: Comparisons of six hypothetical cases suggest that Haldane overestimated the cost of natural selection by allele substitution. The cost is reduced if recessive alleles are advantageous, if substitutions are large and few, if selection is strong and substitutions are rapid, if substitutions are serial, and if substitutions in small demes are followed by deme-group substitutions. But costs are still so heavy that the adaptations of complex organisms in complex and changing environments are never completed. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The life-history traits of Leptoxis suggest that models predicting optimal life-history solutions to specific environmental conditions only are incomplete in that the physiological capabilities of the organism are ignored. Moreover, it is questionable whether precisely optimal life-history strategies can be expected given the likely imprecision of adaptations involving large components of a complex genome and/ or conflicting selection pressures (Darlington 1977). This study suggests that the inclusion of both organismal and environmental constraints in future studies of life-history traits will yield more useful insights into the nature of these complex adaptations.…”
Section: Discussionmentioning
confidence: 96%
“…The life-history traits of Leptoxis suggest that models predicting optimal life-history solutions to specific environmental conditions only are incomplete in that the physiological capabilities of the organism are ignored. Moreover, it is questionable whether precisely optimal life-history strategies can be expected given the likely imprecision of adaptations involving large components of a complex genome and/ or conflicting selection pressures (Darlington 1977). This study suggests that the inclusion of both organismal and environmental constraints in future studies of life-history traits will yield more useful insights into the nature of these complex adaptations.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, it was shown that high mutation rates and mutator strains can emerge naturally during laboratory evolution and contribute to the formation of genetic novelty [33,73,139-141]. It is clear that a higher mutation rate can only be beneficial to a certain extent as it also results in a genetic load [142]. Recent data indicated that long-term adaptation, mediated by an increased mutation rate and genetic load, is tightly balanced in bacterial cultures.…”
Section: Adaptive Laboratory Evolutionmentioning
confidence: 99%
“…Adaptation is an imperfect and imprecise process. In order to survive and reproduce in the face of fluctuating situations, the individual can only try to be better than his rivals by adopting &dquo;adequate,&dquo; &dquo;necessary,&dquo; &dquo;sufficient,&dquo; or &dquo;tolerable&dquo; tactics (55,123,124).…”
Section: The Unpredictability Of Solutionsmentioning
confidence: 99%